2023
DOI: 10.3389/fnut.2023.1075778
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of nutritional support in the supportive care of pediatric patients undergoing hematopoietic stem cell transplantation

Abstract: Allogeneic Hematopoietic Stem Cell Transplantation (allo-HSCT) represents a potentially curative strategy for many oncological, hematological, metabolic, and immunological diseases in children. The continuous effort in ameliorating supportive care represents one of the cornerstones in the improvement of outcome in these patients. Nowadays, more than ever nutritional support can be considered a key feature. Oral feeding in the early post-transplant period is severely impaired because of mucositis due to conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 123 publications
0
17
0
Order By: Relevance
“…In the months leading up to the allo-HCT procedure, induction and consolidation chemotherapies performed to control the underlying disease induces side effects (diarrhea, nausea, mucositis, and infections) that potentiate the disease's catabolic and anorectic effects, harming one's nutritional status. Malnutrition before and during allo-HCT is a recognized risk factor that influences short-term clinical outcome, survival, and GvHD regardless of age [3,4 ▪ ,5,6]. A study evaluated a composite anthropometric score in a pediatric population using a ROC curve.…”
Section: Before the Stormmentioning
confidence: 99%
See 2 more Smart Citations
“…In the months leading up to the allo-HCT procedure, induction and consolidation chemotherapies performed to control the underlying disease induces side effects (diarrhea, nausea, mucositis, and infections) that potentiate the disease's catabolic and anorectic effects, harming one's nutritional status. Malnutrition before and during allo-HCT is a recognized risk factor that influences short-term clinical outcome, survival, and GvHD regardless of age [3,4 ▪ ,5,6]. A study evaluated a composite anthropometric score in a pediatric population using a ROC curve.…”
Section: Before the Stormmentioning
confidence: 99%
“…Furthermore, ESPEN recommends patients maintain physical activity and ensure adequate nutritional intake. Doctors may advice the additional use of oral nutritional supplements when the diet is insufficient to meet nutritional goals, but they have no reported effect on GvHD [4 ▪ ]. Although oral glutamine supplementation was shown to reduce the incidence of GvHD, no studies have confirmed this effect in the last 15 years.…”
Section: Before the Stormmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, OM increases the risk of infection by causing the need for total parenteral nutrition due to oral nutrition intolerance of the patient. Nutritional deficiency caused by mucositis directly contributes to increased mortality in children who have had a transplant [5]. Since patients are immunosuppressed due to chemotherapy, oral lesions can lead to severe, life-threatening sepsis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Children undergoing hematopoietic stem cell transplant (HSCT) are required to follow strict medical regimens, including taking medication, deploying behavioral strategies to minimize infections, and following dietary guidelines. Adhering to these dietary guidelines can be particularly challenging as pre-HSCT conditioning regimens can adversely affect their food intake ( 1 ), much like infections, various medications, and the well-described post-HSCT complication, graft-vs.-host disease ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%